Nitrogen-doped carbon composite derived from ZIF-8/polyaniline@cellulose-derived carbon aerogel for high-performance symmetric supercapacitors. (15th June 2021) - Shang, Mengge; Zhang, Xinen; Zhang, Jing; Sun, Jinqiang; Zhao, Xinfu; Yu, Shimo; Liu, Xiaochan; Liu, Benxue; Yi, Xibin
Highlights: Cellulose derived carbon aerogel coated by PANI used as a scaffolding framework. ZIF-8 derived porous carbon (ZC) is anchored into PCA carbon framework. ZPCA carbon composite has a high specific surface area and large N contents. ZPCA carbon composite yield a large specific capacitance of 388 F g −1 at 0.5 A g −1 . The symmetric device shows ultrahigh energy density in 1 M Et4 NBF4 /AN electrolyte. Abstract: Cellulose derived carbon aerogel (CA) with unique three-dimensional network coated with polyaniline (PANI) on its surface is used as a scaffolding framework to anchor ZIF-8. The designed ZIF-8 derived porous carbon (ZC)/PANI@CA (ZPCA) hybrid carbon composite through a facile solution immersion chemical route and subsequent carbonization process is employed as electrode for supercapacitor, which has contributed a large specific surface area, a hierarchical porous structure and reasonable N content (up to 6.27 at.%). The synthesized ZPCA electrode achieves an outstanding capacitance of 388 F g −1 at 0.5 A g −1 as well as an excellent cycling performance. More inspiringly, the symmetric supercapacitor based ZPCA achieves a high energy density of 13.4 Wh kg −1 at a power density of 250 W kg −1 using 2 M KOH aqueous solution, and an ultrahigh energy density of 81.8 Wh kg −1 at a power density of 950 W kg −1 is realized using Et4 NBF4 /AN electrolyte.